Crystallographic comparison of the estrogen and progesterone receptor’s ligand binding domains - Tanenbaum, David M. (The National Academy of Sciences, 1998)
The 2.8-Å crystal structure of the complex formed by estradiol and the human estrogen receptor-α ligand binding domain (hERαLBD) is described and compared with the recently reported structure of the progesterone complex of the human progesterone receptor ligand binding domain, as well as with similar structures of steroid/nuclear receptor LBDs solved elsewhere. The hormone-bound hERαLBD forms a distinctly different and probably more physiologically important dimer interface than its progesterone counterpart. A comparison of the specificity determinants of hormone binding reveals a common structural theme of mutually supported van der Waals and hydrogen-bonded interactions involving highly conserved residues. The previously suggested mechanism by which the estrogen receptor distinguishes estradiol’s unique 3-hydroxy group from the 3-keto function of most other steroids is now described in atomic detail. Mapping of mutagenesis results points to a coactivator-binding surface that includes the region around the “signature sequence” as well as helix 12, where the ligand-dependent conformation of the activation function 2 core is similar in all previously solved steroid/nuclear receptor LBDs. A peculiar crystal packing event displaces helix 12 in the hERαLBD reported here, suggesting a higher degree of dynamic variability than expected for this critical substructure.